miR-146a-5p Promotes the Inflammatory Response in PBMCs Induced by Microcystin-Leucine-Arginine - Zhang H; Chen D; Ji Q; Yang M; Ding R (Dove Medical Press, 2023)
Huiying Zhang,1,* Daojun Chen,1,2,* Qianqian Ji,1 Meiyan Yang,1 Rui Ding1 1Department of Occupational Health and Environmental Health, School of Public Health, Anhui Medical University, Hefei, Anhui, 230032, People's Republic of China; 2School of Medical Technology, Anhui Medical College, Hefei, Anhui, 230601, People's Republic of China*These authors contributed equally to this workCorrespondence: Daojun Chen, Email daodaodao1978@163.comBackground: Microcystin-leucine-arginine (MC-LR) is the most abundant and most toxic variant of microcystin isomers. Various experiments have clearly shown that MC-LR has hepatotoxicity and carcinogenicity, but there are relatively few studies on its immune damage effect. In addition, numerous studies have shown that microRNAs (miRNAs) are involved in a wide range of biological processes. Do miRNAs also play a role in inflammatory response caused by microcystin exposure? This is the question to be answered in this study. Moreover, this study can also provides experimental evidence for the significance of miRNA applications.Objective: To investigate the effect of MC-LR on the expressions of miR-146a and pro/anti-inflammatory cytokines in human peripheral blood mononuclear cells (PBMCs) and to further explore the role of miR-146a in the inflammatory responses caused by MC-LR.Methods: Serum samples from 1789 medical examiners were collected and detect the concentrations of MCs, and 30 serum samples with concentrations of MCs around P25, P50, and p75 were randomly selected for the detection of inflammatory factors. PBMCs from fresh peripheral blood extracted from these 90 medical examiners were subsequently tested for relative miR-146a expression. In vitro, the MC-LR were exposed to the PBMCs to detect the levels of inflammatory factors as well as the relative expression of miR-146a-5p. Then, a miRNA transfection assay was performed to verify the regulation of inflammatory factors by miR-146a-5p.Results: In population samples, the expression of inflammatory factors and miR-146a-5p increased with increasing MCs concentration. In vitro experiments showed that the expression of inflammatory factors and miR-146a-5p in PBMCs increased with MC-LR exposure time or exposure dose too. In addition, inhibiting the expression of miR-146a-5p in PBMCs reduced inflammatory factor levels.Conclusion: miR-146a-5p exerts a promoting effect on the MC-LR-induced inflammatory response by positively regulating inflammatory factor levels.Keywords: microcystin-leucine-arginine, MC-LR, human peripheral blood, mononuclear cells, PBMCs, miR-146a, inflammatory cytokines